REVITALISASI UKM KERAJINAN KAYU BERBASIS TEKNOLOGI DI DESA PETULU UBUD GIANYAR - Made Agung Raharja (Bhakti Persada Jurnal Aplikasi IPTEKS, 2018)
Ubud sub-district has individual companies or SMEs belonging to the most from other areas. In the implementation of Ipteks Bagi Produk Ekspor (IbPE) in the first implementation year there are 3 (Three) partners who will be accompanied in Petulu Village, Ubud sub-district, Gianyar regency, Bali province. The third type of SMEs are SMEs of Wood Crafts. With this method the expected outcomes from partners are: 1) Increased SME marketing skill in terms of the use of Internet-based information technology using online e-commers application. 2) Improvement of SME business management capability and Mastery. The results of this IbPE activity are: (1) Installation and facilitation of website marketing (e-commerce) can run well. (2) The implementation of SME management training activities has provided insight into knowledge and skills to the owners of SMEs (3) Initial guidance of foreign language assistance may work well and needs to be done to provide a good understanding for the owners or employees of SMEs.